2013
DOI: 10.2478/s11687-013-0101-y
|View full text |Cite
|
Sign up to set email alerts
|

Organic amendments of soil as useful tools of plant parasitic nematodes control

Abstract: Use of organic soil amendments is a traditional agricultural practice for improving physical and chemical soil properties, soil structure, temperature and humidity conditions as well as nutrients content which are needful for plants growth. Application of organic materials to soil can cause a change in soil microflora and microfauna including soil nematodes. Nematodes, are the most ample and varied group of soil fauna. They are ever-present habitants of all soil types with high population densities. The change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 126 publications
1
23
0
Order By: Relevance
“…Two predatory nematode genera were found: Clarkus and Mylonchulus ( Figure 5). Distribution of predatory nematodes was random which is in line with earlier data published by Renčo and Kováčik (2012). So we cannot explain reduced Meloidogyne damage on the roots of the mulched plants with the presence and density of potential antagonist nematodes in our experiment.…”
Section: Resultssupporting
confidence: 79%
“…Two predatory nematode genera were found: Clarkus and Mylonchulus ( Figure 5). Distribution of predatory nematodes was random which is in line with earlier data published by Renčo and Kováčik (2012). So we cannot explain reduced Meloidogyne damage on the roots of the mulched plants with the presence and density of potential antagonist nematodes in our experiment.…”
Section: Resultssupporting
confidence: 79%
“…In every case our data show that to obtain good quality reproduction material as expected by international olive tree industries it is necessary to apply good sanitation practices in olive tree nurseries. The use of resistant olive rootstock or cultivars selected by rapid screening trials for the resistance to the root-knot nematodes (Sasanelli et al, 2000) or the use of olive residues derived from pruning or olive oil extraction (Renčo, 2013) can minimize or limit the damage of nematode infections in nurseries although it may cause a selection of more virulent root-knot nematode populations capable of circumventing resistance to olive plants grown in poor sanitation conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Organic amendment may have different effects on different soil microbial groups, and nematodes could be reduced by such a modified microbial group [119,121]. The prokaryotic community structure of the treatments reported by Wang [82] was evaluated, and the results showed that Mix2 treatment, in which low NO 3 − risk and high nematode suppression were confirmed, was separated from the other treatments, indicating that a specific microbial community was developed in the treatment (Figure 2).…”
Section: Effect Of Biogas Digestate Application On Root-knot Nematodementioning
confidence: 97%
“…For instance, Bulluck [117] also observed that Dry Anaerobic Digestion for Agricultural Waste Recycling DOI: http://dx.doi.org/10.5772/intechopen.91229 M. incognita populations were not affected by amendments of swine manure and composts. There are several factors which determine the effect of organic fertilizer on plant-parasitic nematodes, and the most commonly reported one is C/N ratio [119]. Organic amendment with a C/N ratio in the range of 15-20 was considered most effective [114].…”
Section: Effect Of Biogas Digestate Application On Root-knot Nematodementioning
confidence: 99%